The effects of bleed on gas turbine performance. - Hackney, Richard James (Cranfield University, 2018)
Comparison of the alternative method against a compressor ’splitting’ method showed comparable, and at off-design conditions, better, results can be obtained with the need for extensive manual model adjustment that the splitting method requires. This method has been implemented in 0-D cycle analysis software, which uses thermodynamic principles and component maps to calculate engine performance. Such a model tends to be used to analyse the overall effects of a component change on the engine cycle in a rapid and low-complexity manner (at a range of off-design conditions), whilst still producing a satisfactory level of accuracy. In the initial stages of a design project, the quick analysis and results from the 0-D software are essential to narrow down design choices and to analyse off-design performance. In this respect, the alternative method offers an enhancement to current methods for modelling bleed in the gas turbine. Using this method to vary bleed stage and amount has been shown to change the engine running line and hence surge margin. This method can be used to produce three-dimensional plots showing the combined effect of bleed amount and offtake stage location at a range of fixed parameters according to the user requirements (e.g. fixed speed, temperature or massflow).
Keywords: Compressor; bleed; modelling; secondary air system; turbomatch; offtake